Aging performance evaluation of vacuum insulation panel (VIP). (December 2017) - Kim, Jin-Hee; Boafo, Fred Edmond; Kim, Sang-Myung; Kim, Jun-Tae
Abstract: Energy efficiency solutions are being pursued as a sustainable approach to reducing energy consumption and related gas emissions across various sectors of the economy. Vacuum Insulation Panel (VIP) is an energy efficient advanced insulation system that facilitates slim but high-performance insulation, based on a porous core material evacuated and encapsulated in a barrier envelope. Although VIP has been on the market for decades now, it wasn't until recently that efforts have been initiated to propose and adopt a global standard on characterization and testing. One of the issues regarding VIP is its durability and aging due to pressure and moisture dependent increase of the initial low thermal conductivity with time; more so in building applications. In this paper, the aging performance of commercially available VIP was investigated experimentally; thermal conductivity was tested in accordance with ISO 8302 standard (guarded hot plate method) and their long-term performance was analyzed based on a non-linear pressure-humidity dependent equation based on IEA/EBC Annex 39, with the aim of evaluating durability of VIP. The center-of-panel thermal conductivity after 25 years based on initial 90% fractile with a confidence level of 90% for the thermal conductivity ( λ 90/90 ) ranged from 7.3–8.2 mW/(m K) for silica core VIP. Significant differences between manufacturer-provided data and measurements of thermal conductivity and internal pressure were observed.